The Role of Leadership Style and Motivation in Improving Employee Performance of Village Owned Enterprises - Dimas Risna Triasmawan; Nurul Qomariah; Haris Hermawan (Budapest International Research and Critics University, 2023)
BUMDes currently has a role in increasing economic activity in rural areas in the leasing business, microfinance services. This study aims to determine and analyze the effect of leadership style and motivation on employee performance at BUMDes Pontang Village, Ambulu District, and Jember. The population in this study were all employees of Pontang Ambulu Village Owned Enterprises, totaling 41 employees, all of whom were used as samples (saturated sampling). Data analysis used descriptive analysis and multiple linear regressions. Validity test and reliability test were also used to test the research questionnaire. The results of the analysis show that a leadership style that can set an example to subordinates has an effect on employee performance. Work motivation has a positive impact on the performance of employees of Pontang Ambulu Village-Owned Enterprises, Jember.